Analysis of Efficiency of Government Expenditure In Health Sector in Central Java Province in 2012-2014 - Eka Dian Puspitasari; Amin Pujiati (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2017)
Health is one of the important factors in the success of the economic development in a country. The Government has managed the health budgets of at least ten percent of the total of the available local government budget. However, the amount of health budget has not been balanced yet by the optimal achievement of health status. This research aims at analyzing the technical efficiency level of the expenditure cost and the health service system and the target of improvement in order to achieve the efficiency in Central Java province in 2012-2014. This research uses Data Envelopment Analysis (DEA) method that will yield a relative efficiency value. The research uses health budget as the input variable, uses facilities and health services as the intermediate output variable, and uses the health status as the outcome variable. The assumption used is: Variable Return to Scale (VRS) and the output oriented model. The results of research that use the DEA method show that with the cost technical efficiency there are only five regencies/cities (14.3%) that have achieved an efficiency of 100 percent. While with the system technical efficiency there are only eleven regencies/cities (31.4%) that have achieved an efficient condition. This means, most regencies/cities in Central Java Province have not still efficient yet in the use of expenditure of health sector budget.